PENGARUH KUALITAS PELAYANAN, KERAGAMAN PRODUK, DAN LOKASI TERHADAP KEPUASAN KONSUMEN: (STUDI PADA APOTEK K-24 KADIPIRO YOGYAKARTA) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2022)
This research is motivated by the community need for everything related to health. In addition to wanting to get the desired product, people also expect good and excellent service from product providers, in this case are pharmacy employees. In addition, a strategic, safe and comfortable location is a benchmark for whether the community is satisfied with what has been offered by the pharmacy. This study aims to determine and analyze the effect of service quality, product diversity, and location at Apotek K-24 Kadipiro Yogyakarta. The sample of this research is consumers who have purchased a product at Apotek K-24 Kadipiro Yogyakarta at least once. The sampling technique used is purposive sampling, which is a sample research technique with certain considerations that have been determined in advance by the researcher. The statistical analysis method consisted of multiple linear regression analysis, simultaneous significant testing (F test), partial significant testing (t test), and determination analysis (R2). The analysis of determination test (R2) states the value of Adjusted R Square is 55.3%. This means that the variables of service quality, product diversity, and location on consumer satisfaction have a contribution of 55.3%. Partial testing (t test) is known that the variables of service quality, product diversity, and location have a significant effect on customer satisfaction. Simultaneous testing (F test) is known that the variables of service quality, product diversity, and location together (simultaneously) have a significant effect on customer satisfaction.
Keywords: service quality; product diversity; location